Prediction of occupational exposure limits for noise-induced non-auditory effects. (February 2022) - Golmohammadi, Rostam; Darvishi, Ebrahim; Shafiee Motlagh, Masoud; Faradmal, Javad; Aliabadi, Mohsen; Rodrigues, Matilde A.
Abstract: There is a recent trend to place more emphasis on noise non-auditory effects. Despite its implications on health, there is a lack of recommendations for noise in occupational settings. This study aimed to present occupational exposure limits for noise-induced non-auditory effects in healthy males using empirical exposure-response regression models based on the data of laboratory and ﬁeld considering the effective variables. To this end, the equivalent noise level was measured and recorded in four working settings including closed offices, open-plan offices, control rooms, and industrial workplaces during a normal working day. They were 65, 68, 73, and 80dB(A), respectively. In the laboratory, 31 healthy males were exposed to five noise conditions (four noisy conditions and one quiet) during 8 h and they were asked to perform the cognitive tests. In the ﬁeld phase, 124 healthy males were also examined from four working settings in their workstations for 8 h. The psychophysiological parameters of the participants were recorded in both lab and field. The results indicated variations in mental responses at levels above 55dBA, and psychophysiological variations at levels above 70dB(A) in both phases. The findings also showed that the developed regression models could plausibly predict the noise-induced psychophysiological responses during exposure to noise levels; thus, they can be presented the likely exposure limits. Based on the results of the models, the levels <55dB(A) are likelihood of the acoustic comfort limit, and the levels ranged from 55 to 65dB(A) are the acoustic safe limits. The acoustic caution limit is the likelihood of the levels ranged from 65 to 75dB(A). The levels ranged from 75 to 80dB(A) are likely the action levels or control limits, and the occupational exposure limit are the probability of levels> 80dB(A). Graphical abstract: Image 1 Highlights: Comfort and cognitive performance are disrupted in occupational noise levels higher than 55dB(A). The stress responses (e.g. increase electro dermal activity and cortisol) are likely manifested in noise levels higher than 65dB(A). The physiological responses (e.g. heart rate variability and respiration rate) are likely manifested in noise levels higher than 70dB(A). Acoustic comfort limit is the levels <55dB(A). The acoustic safe limit is ranged from 55 to 65dB(A). The acoustic caution limit and the acoustic action limit range between 65–75 and 75–80dB(A), respectively. The acoustic exposure limit is >80dB(A).